Evaluasi Program Pembelajaran Bahasa Inggris di Sekolah Dasar - Laely Nuriyah (Jurnal Ilmiah Wahana Pendidikan, 2021)
The aims of this research were to evaluate English learning in context, input, process, product. This research was an evaluation research. The sources of the research were students of English for Children class at SD Al Farhan. The data was collected through observation, test, and documentation which was analyzed descriptive quantitative. The conclusions in this research were: 1) the of context value of sub component at the pre-condition is fair, the input value of component sub component infrastructure, human resources and curriculum is poor, the result of process component sub component of planning and English learning implementation is fair, and the product component value in the learning result of the students is fair, and 2) the recommendation of this research, the general manager needs to observe and change the curriculum for a better future, then provide laboratory room for listening, the teachers should make a lesson plan based on the syllabus for each competency